Studi Komparasi Bangunan Tahan Gempa Berdasarkan SNI 1726-2012 dan SNI 1726-2019 : Studi Kasus: Bangunan Gedung 8 Lantai - Pramesta Armanisag P; Agustinus Sungsang Nana P; Hida Ulfa A (Fakultas Teknik Universitas Cenderawasih, 2024)
Indonesia is an archipelago that is flanked by oceanic plates and land plates that cause the two plates to often collide. This causes Indonesia to be an earthquake-prone area and has many volcanoes. Research related to earthquakes in Indonesia continues to develop. This has resulted in several points such as new earthquake hazard maps and the latest regulations related to earthquake-resistant building planning, resulting in the building planning process having to follow the latest applicable regulations. The purpose of this study is to analyze changes in SNI, structural dimension requirements, reinforcement requirements, and structural behavior and internal forces due to the application of SNI 1726:2012 and SNI 1726:2019 in a building. The research method used was to conduct a literature study on the changes from SNI 1726:2012 to SNI 1726:2019 using the SNI 2847:2019 planning which will be used in the structural analysis. The results obtained from this study show that there are differences in the earthquake maps used in SNI 1726:2012 and SNI 1726:2019, there are differences in parameters in SNI 1726:2012 and SNI 1726:2019 which result in an increase in the forces acting on the structure which affects the need for reinforcement. Structural planning is carried out by following SNI 1726:2019 and SNI 2847:2019, for existing buildings that have been built based on SNI 1726:2012, it is necessary to carry out a re-examination or assessment to determine the condition of the existing building in relation to earthquake in Indonesia.